2007
DOI: 10.4103/0970-9371.41899
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of fine needle aspiration cytology in subtyping breast malignancies - a report of three cases

Abstract: A 55 years old female came with a lump in the right breast since 1 year. Clinical examination revealed a large mass in the right breast, firm to hard in consistency measuring 6x5.5x5cm. The mass was fixed to the underlying structures. Skin over the mass was red and ulcerated destroying the nipple and areola. A clinical diagnosis of carcinoma of breast was made. FNAC of the mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Therefore, the results must be carefully assessed [35], due to certain limitations of FNAC which require final histopathological diagnosis for establishing prognosis and therapy. The key point is to determine the diagnostic accuracy of FNA cytology and to develop distinguishing cytologic criteria addressing the diagnostic challenges [51]. Karim et al showed in rats an FNA sensitivity of 92.3% and specificity of 89.4% for the detection of malignancy in comparison with histologic diagnosis of tissue biopsies.…”
Section: Sensitivity and False Positive Or Negative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the results must be carefully assessed [35], due to certain limitations of FNAC which require final histopathological diagnosis for establishing prognosis and therapy. The key point is to determine the diagnostic accuracy of FNA cytology and to develop distinguishing cytologic criteria addressing the diagnostic challenges [51]. Karim et al showed in rats an FNA sensitivity of 92.3% and specificity of 89.4% for the detection of malignancy in comparison with histologic diagnosis of tissue biopsies.…”
Section: Sensitivity and False Positive Or Negative Resultsmentioning
confidence: 99%
“…Careful assessment of cytological features of squamous cells and the appearance of the background is crucial for achieving a correct di-agnosis. Deep knowledge of the cytomorphology and cytodiagnosis of rare breast malignant tumors is crucial in the FNA analysis [51].…”
Section: Sensitivity and False Positive Or Negative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,13 FNAC has certain limitations as it is difficult to subtype breast malignancies. 6,7,9 CONCLUSION FNAC is a safe outpatient procedure, which is cost effective. Our study shows most of the breast lesions are benign and needs only reassurance and early diagnosis to prevent patients discomfort and anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Although today, breast cyst aspiration is a routine procedure 14 , evaluation of nonbloody cyst fluidcan at times be of non diagnostic value 15 .False Negative Cytologic Diagnosis of Breast Carcinoma has also been described 16 .…”
mentioning
confidence: 99%